An Analysis of Direct Hippocampal Cortical Field CA1 Axonal Projections to Diencephalon in the Rat - Cenquizca, Lee A. (2006)
The hippocampal formation is generally considered essential for processing episodic memory. However, the structural organization of hippocampal afferent and efferent axonal connections is still not completely understood, although such information is critical to support functional hypotheses. The full extent of axonal projections from field CA1 to the interbrain (diencephalon) is analyzed here with the Phaseolus vulgaris-leucoagglutinin (PHAL) method. The ventral pole of field CA1 establishes direct pathways to, and terminal fields within, the anterior hypothalamic nucleus, ventromedial hypothalamic nucleus, lateral hypothalamic and lateral preoptic areas, medial preoptic area, and certain other hypothalamic regions, as well as particular midline thalamic nuclei. These results suggest that hippocampal field CA1 modulates motivated or goal-directed behaviors, and physiological responses, associated with the targeted hypothalamic neuron populations.